Varied Contribution of Phospholipid Shedding From Membrane to Daptomycin Tolerance in Staphylococcus aureus - Shen, Tianwei; Hines, Kelly M.; Ashford, Nathaniel K.; Werth, Brian J.; Xu, Libin (Frontiers in Molecular Biosciences, 2021)
It has been suggested that daptomycin can be inactivated by lipids released by Staphylococcus aureus and that this effect is antagonized by phenol soluble modulins (PSMs), which bind to the shed lipids. PSM production is regulated by the Agr system, and others have shown that loss of the Agr function enhances S. aureus survival in the presence of daptomycin. Here we assessed the impact of Agr function on daptomycin activity and lipid metabolism under various conditions. Daptomycin activity was evaluated against three series of isogenic strain series with wild-type or dysfunctional Agr using static daptomycin time-kills over 24 hrs and against one strain pair using in vitro pharmacokinetic/pharmacodynamic (PK/PD) models simulating clinical daptomycin exposure for 48 hrs. We performed comprehensive lipidomics on bacterial membranes and the spent media to correlate lipid shedding with survival. In static time-kill experiments, two agr-deficient strains (SH1000- and USA300 LAC ΔagrA) showed improved survival for 8 hrs compared with their corresponding wild-type strains as seen in previous studies, but this difference did not persist for 24 hrs. However, four other agr-deficient strains (SH1001 and JE2 agr KOs) did not demonstrate improved survival compared to isogenic wild-type strains at any time in the time-kills. Lipidomics analysis of SH1000, SH1001, and SH1000- strains showed daptomycin exposure increased lipid shedding compared to growth controls in all strains with phosphatidylglycerols (PGs), lysylPGs and cardiolipins predominating. In the cell pellets, PGs and lysylPGs decreased but cardiolipins were unchanged with daptomycin exposure. The shed lipid profiles in SH1001 and SH1000- were similar, suggesting that the inability to resist daptomycin by SH1001 was not because of differences in lipid shedding. In the PK/PD model, the agr mutant SH1000- strain did not show improved survival relative to SH1000 either. In conclusion, inactivation of daptomycin by shed lipids may be dependent on genetic background, the specific agr mutations, or the techniques used to generate these KOs rather than the overall function of the Agr system, and its contribution to daptomycin tolerance seems to be varied, transient, and growth-condition dependent.